The safety and efficacy of nasobiliary drainage versus biliary stenting in malignant biliary obstruction: A systematic review and meta-analysis. Issue 46 (November 2016) - Lin, Huapeng; Li, Shengwei; Liu, Xi
Abstract : Supplemental Digital Content is available in the text Abstract: Background: Preoperative biliary drainage (PBD) has been widely used to treat patients with malignant biliary obstruction. However, it is still unclear which method of PBD (endoscopic nasobiliary drainage or endoscopic biliary stenting) is more effective. Thus, we carried out a meta-analysis to compare the safety and efficacy of endoscopic nasobiliary drainage (ENBD) and endoscopic biliary stenting (EBS) in malignant biliary obstruction in terms of preoperative and postoperative complications. Methods: We conducted a literature search of EMBASE databases, PubMed, and the Cochrane Library to identify relevant available articles that were published in English, and we then compared ENBD and EBS in malignant biliary obstruction patients. The preoperative cholangitis rate, the preoperative pancreatitis rate, the incidence of stent dysfunction, the postoperative pancreatic fistula rate, and morbidity were analyzed. Odds ratios (ORs) with 95% confidence intervals (CIs) were used to express the pooled effect on dichotomous variables, and the pooled analyses were performed using RevMan 5.3. Results: Seven published studies (n = 925 patients) were included in this meta-analysis. We determined that patients with malignant biliary obstruction who received ENBD had reductions in the preoperative cholangitis rate (OR = 0.35, 95% CI = 0.25–0.51, P < 0.0001), the postoperative pancreatic fistula rate (OR = 0.38, 95% CI = 0.18–0.82, P = 0.01), the incidence of stent dysfunction (OR = 0.39, 95% CI = 0.28–0.56, P < 0.0001), and morbidity (OR = 0.47, 95% CI = 0.27–0.82, P = 0.008) compared with patients who received EBS. Conclusions: The current meta-analysis suggests that ENBD is better than EBS for malignant biliary obstruction in terms of the preoperative cholangitis rate, the postoperative pancreatic fistula rate, the incidence of stent dysfunction, and morbidity. However, a limitation is that there are no data from randomized controlled trials.